The acid mine drainage potential of the Platreef, Northern Limb of the Bushveld Complex, South Africa - Lishman, Katherine Louise (My University, 2010)
The Acid Mine Drainage (AMD) potential of rocks at an exploration project on the Platreef in the northern limb of the Bushveld Complex has been investigated. The Platreef Project, at an advanced stage of exploration, is located north of Mokopane in the Limpopo Province of South Africa. A total of 242 samples were selected from borehole core and 11 tailings samples were obtained from Mintek Laboratory. Quality control samples were inserted and all the rock samples were dispatched for whole rock geochemistry and static Acid Base Accounting (ABA) analysis. Once the static ABA results were received, a sub-set of 20 samples was selected for kinetic test analysis. Of the tailings samples, three were sent for whole rock geochemistry analysis, six for static ABA analysis and five for kinetic test analysis. Using criteria developed within the context of coal mining in South Africa and based on international criteria, the static ABA results were used to classify the rocks according to acid producing potential. These results revealed that high risk acid producing (Pegmatitic Gabbro-Norite, Melanorite, Norite Cycles, Feldspathic Pyroxenite, Hornfels and Marginal Zone Norite) and low risk acid producing rock-types (Pyroxenite, Dolerite, Quartz Feldspar, Aplite) may be mined at the Platreef site. The kinetic test and whole rock geochemistry results provided further insight into the acid producing potential of the rock types and revealed that Gabbro-Norite and Dolomite (altered to Calcsilicate Hornfels) have the potential to generate acid despite being classified as non-acid generating/potentially acid neutralizing. The tailings results proved contradictory and this is thought to be due to non-representative sampling. It is recommended that a new suite of representative tailings samples be generated and sent for static ABA and kinetic test analysis once the metallurgical treatment process has been finalised. Future work should be directed to better understand the merits and downfalls of the different analytical methods used to quantify AMD in order to better interpret contradictory results. This laboratory based analysis of AMD potential provides a “worse case scenario” of the rock types to be mined. Weighted volume calculations of the mean sulphur content and the mean Net Neutralising Potential (Closed) of material to be mined initially on Turfspruit indicate that it is unlikely that AMD will be generated from the tailings dams or waste rock piles generated from mining in this region. This study has shown, however, that AMD could result if high risk acid producing Platreef material is stockpiled at the site prior to treatment for extended periods of time. Local zones of potentially acid-producing material may occur within rock volumes dumped over the Life of Mine (Marginal Zone Norite, Hornfels, Gabbro-Norite, and Dolomite) or exposed in the pit floor (Marginal Zone Norite, Hornfels, Dolomite), and these should be managed carefully to ensure that AMD does not result. The Quartzite samples produced contradictory results during this study and, as this rock type occurs in the Footwall to the Platreef, it is recommended that further Quartzite samples be sent for static ABA and kinetic test analyses. This study has identified the potential AMD risks facing the future mine at the Platreef Project and will enable the mine management to minimize these risks during the mine design phase. These results should fit into a larger framework of objectives and on-site conditions with time in order to effectively manage AMD risk over the Life of Mine.